Analysis of risk factors predicting recurrence of chronic subdural hematoma - Yogi, Nikunja; Nepal, Pankaj Raj; Gongal, Dinesh Nath; Devkota, Upendra Prasad (Nepal Journal of Neuroscience, 2018)
Recurrences after evacuation of chronic subdural hematoma are seen in 2-33% of cases with various surgical approaches. Various demographical, clinical, radiological, surgical and postoperative management strategies have been explored as the possible predictors of recurrence.We performed a retrospective analysis in 160 patients with chronic subdural hematoma with an aim to analyze the post-operative recurrences and factors associated with it. Various socio demographic and clinico-radiological parameters were studied against the rate of recurrence after surgery using Chi square/Fischer Exact Test. Factors showing significant association on univarate analysis were then analysed using binary logistic regression.The rate of recurrence of CSDH in our study was 5% and the mean duration of recurrence was 33 days. Chronic alcohol use (p=0.007) and intraoperative brain expansion ((p=0.001) were the two factors associated with recurrence of CSDH. On binary logistic regression chronic alcohol use (wald-6.467, p=0.011) and intraoperative brain expansion (wald=6.674, p=0.010) were both associated significantly with recurrence of CSDGH with an odds of 7.804 and 0.058 respectively.